2009
DOI: 10.1063/1.3256140
|View full text |Cite
|
Sign up to set email alerts
|

Blue luminescence of SrTiO3 under intense optical excitation

Abstract: The blue-green photoluminescence emitted by pure and electron-doped strontium titanate under intense pulsed near-ultraviolet excitation is studied experimentally as a function of excitation intensity and temperature. Both emission spectra and time-resolved decays of the emission are measured and analyzed in the framework of simple phenomenological models. We find an interesting blue-to-green transition occurring for increasing temperatures in pure samples, which is absent in doped materials. The luminescence y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 43 publications
10
27
0
Order By: Relevance
“…In addition, we observe a quite unusual pump-fluence behavior: at high carrier concentrations, an increase of the lifetime is observed, contrary to a lifetime decrease expected from bimolecular and/or Auger recombination mechanisms. 22 Both observations are consistent with previous studies covering millisecond time windows with nanosecond time resolution. 10,11 The relaxation and recombination mechanism of photogenerated carriers in 3C-SiC is not yet well understood and requires further studies, beyond the scope of the present work.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…In addition, we observe a quite unusual pump-fluence behavior: at high carrier concentrations, an increase of the lifetime is observed, contrary to a lifetime decrease expected from bimolecular and/or Auger recombination mechanisms. 22 Both observations are consistent with previous studies covering millisecond time windows with nanosecond time resolution. 10,11 The relaxation and recombination mechanism of photogenerated carriers in 3C-SiC is not yet well understood and requires further studies, beyond the scope of the present work.…”
supporting
confidence: 82%
“…By varying the pump fluence, we do not observe a charge-density dependence of the relaxation dynamics. This observation suggests a unimolecular recombination mechanism, for example via defect states: the photoinduced carrier population consists of several distinct subpopulations, each obeying an exponential decay law with different decay constant 22 . Possibly, different excitation mechanisms (for instance nanosecond versus femtosecond pulses) enhance one population with respect to another.…”
mentioning
confidence: 99%
“…15,16 However, there is still controversy about the underlying luminescence processes responsible for each emission band. 17 The accelerating voltage used to excite the CL signal is directly related to the electron penetration depth below the surface. We have carried out simulations of the penetration depth profiles using the CASINO software package 18 for 5 and 10 keV electrons in STO.…”
Section: Resultsmentioning
confidence: 99%
“…pairs [49]. Further, the secondary spin 6 ] clusters and so Cr 3? ion tend to occupy octahedral sites [1].…”
Section: Electron Paramagnetic Resonancementioning
confidence: 96%
“…SrTiO 3 has wide band gap (3.2 eV) and further, the optical band gap can be tuned by doping suitable transition metal (TM) ions. The enhancement of optical property of TM doped SrTiO 3 has been extensively studied and elucidated the possibility of the blue, red, green and yellow emission in the SrTiO 3 compounds [6][7][8]. Further, Alvarado et al [9] reported that the electroluminescence spectra of Cr doped SrTiO 3 was arises due to positioning of Cr 3? in an octahedral ligand field which influences the resistive switching process by involving trapping and detrapping of electrons at the Cr site.…”
Section: Introductionmentioning
confidence: 97%